Consumption of Oxidized and Partially Hydrogenated Oils Differentially Induces Trans-Fatty Acids Incorporation in Rats' Heart and Dyslipidemia. (17th February 2016) - Dhibi, Madiha; Mnari, Amira; Brahmi, Faten; Houas, Zohra; Chargui, Issam; Kharroubi, Wafa; Hammami, Mohamed
Abstract : Objectives : A direct effect of process-induced trans -fatty acids (TFAs) on nonalcoholic fatty liver disease (NAFLD) as a cardiovascular disease (CVD) risk factor has previously been shown. We hypothesized that TFAs directly induced CVD. This article describes an investigation of the association between TFAs, provided by the consumption of oxidized soybean oil and margarine, and plasma lipid profiles, coronary artery lesions, and coronary fatty acids distribution in rats. Male rats were fed a standard chow or high-fat diet containing different TFA levels ranging from <1%, <2%, and >2% of total fat in fresh soybean oil, oxidized soybean oil, and margarine, respectively, for 4 weeks. Results : The results indicated that the high-fat diets differently changed the plasma lipid profiles by significantlt increasing triglycerides, total cholesterol, low-density lipoprotein cholesterol, and the ratio of low-density to high-density lipoprotein cholesterol compared to control rats. Compared to fresh soybean oil, oxidized oil further increased plasma lipid markers. The strongest inflammatory effect was induced by margarine, which contains the highest level of TFAs, or 2% of total fat. Total TFAs in the heart of the margarine-fed group were increased by 4.7 regarding to control and by 2.17 and 2.6 relative to groups receiving oxidized and fresh oil, respectively. Increased TFAs consumption was associated with increased histological aspects of atherosclerotic lesions in a dose-dependent manner. Conclusion : In conclusion, process-induced TFAs cause changes including proatherogenic plasma lipid markers, heart fatty acid profiles, and coronary artery histology depending on the TFA level in the supplemented fat and therefore on the type of technological process used.